Perancangan Desain UI/UX Aplikasi Konsultasi Kesehatan Online Dengan Menggunakan Metode Design Thinking (Studi Kasus : Puskesmas Adiarsa) - Ibrahim, Nur; Yusup, Dadang; Carudin, Carudin (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
Adiarsa Health Center is one of the health centers located in West Java, precisely on wirasaba street, East Karawang Regency. Treatment at the Adiarsa Community Health Center can be said to still have several issues, among which is the absence of media or information for teenage patients, where for teenage patients the media is a very important source of information. Based on this, media is needed to facilitate consultation needs. When designing an application, the main factor that is most considered is the user interface design. In designing the user interface using the approach of design thinking, and in testing using the system usability scale (SUS). The design thinking methodology, which comprises five stages empathize, define, ideate, prototype, and test is applied in this study. The results of this research produced a prototype user interface design for an online health consultation application and in the testing stage obtained a SUS score of 75,5. These findings suggest that creating the user interface and user experience of the online health consultation application using the design thingking method can meet user needs and is easy to use.